Impaired Extinction of Learned Contextual Fear Memory in Early Growth Response 1 Knockout Mice - Han, Seungrie (Korea Society for Molecular and Cellular Biology, 2014)
Inductive expression of early growth response 1 (Egr-1) in neurons is associated with many forms of neuronal activity. However, only a few Egr-1 target genes are known in the brain. The results of this study demonstrate that Egr-1 knockout (KO) mice display impaired contextual extinction learning and normal fear acquisition relative to wild-type (WT) control animals. Genome-wide microarray experiments revealed 368 differentially expressed genes in the hippocampus of Egr-1 WT exposed to different phases of a fear conditioning paradigm compared to gene expression profiles in the hippocampus of KO mice. Some of genes, such as serotonin receptor 2C (Htr2c), neuropeptide B (Npb), neuronal PAS domain protein 4 (Npas4), NPY receptor Y1 (Npy1r), fatty acid binding protein 7 (Fabp7), and neuropeptide Y (Npy) are known to regulate processing of fearful memories, and promoter analyses demonstrated that several of these genes contained Egr-1 binding sites. This study provides a useful list of potential Egr-1 target genes which may be regulated during fear memory processing.